Comitê Regional de Prevenção da Mortalidade Infantil: uma análise sob o olhar dos profissionais de saúde - Damasceno, Brena Jéssica Da Silva (2022)
Infant mortality is a public health problem, remaining constant over the yearsin the country, especially in the northeast region. As a result, Committees for the Prevention of Infant Mortality were created, a strategy aimed at identifying infant deaths and designing interventions to prevent the recurrence of new infant deaths. Therefore, this study aims to analyze, from the point of view of health professionals, the role of the regional committee for the prevention of infant mortality in the State of Ceará. For this, a descriptive, exploratory field study was carried out, with a qualitative approach, with members and former members of the Regional Committee for the Prevention of Infant Mortality located in the State of Ceará and health professionals who have already experienced the process of investigating infant deaths.Data collection took place in two stages: document analysis, through the exploration of documents, minutes and reports at the Regional Health Coordination of the State of Ceará, in which the documents belonging to the Regional Committee for the Prevention of Maternal and Child Mortality are archived and Fetal. After presenting the research and inviting the participants, a semi-structured interview was applied. Data analysis took place through content analysis. Since it involves research with human beings, the present research was approved by the Research Ethics Committee of the Federal University of Ceará through opinion Nº. 4.912.159. From the document analysis, through the minutes of the meetings prepared by the committee, it was possible to identify the main recommendations for preventable deaths, highlighting the active search for pregnant women who missed prenatal care and the availability of vacancies in neonatal ICU beds. in tertiary service. The results show the articulation with primary health care, where the entire investigation process begins. The main causes of infant mortality in the region according to the participants consisted of respiratory disorders and congenital malformations, with a high prevalence of deaths from preventable causes. The lack of disclosure of information on the actions carried out by the committee is highlighted. In general, the participants emphasize, among the benefits arising from the committee's performance, the detection of infant deaths and the causes associated with it, also proposing to bring committee members closer to professionals, through monitoring and evaluation actions. performed activities. It should be noted that the committee's performance was impaired due to the pandemic context established in 2020, leading to the suspension of activities and compromising the investigation of deaths in the region. It is concluded that the performance of the committee consists of a fundamental activity for the prevention of infant mortality, which takes place through the surveillance of infant death, planning strategies for the prevention of new deaths and elaboration of recommendations for the health services, whose actions have repercussions on all spheres of society.